Use Of Cryoprotectants In Enhancing Viability Of Probiotic Lactobacillus Strains During Freeze-Drying And Storage - Khoramnia, Anahita (2007)
In recent years, probiotics have been considered to be used as feed supplements to improve the health and growth performance of poultry in place of antibiotic growth promoters. This is due to concerns that the rampant use of antibiotic growth promoters in livestock, particularly poultry, may produce adverse effects on humans, such as the development of antibiotic resistant bacteria and production of antibiotic residues in animal products. Unlike probiotics for humans, which are usually kept refrigerated, probiotics for poultry are normally kept in the farm at room temperature, and this may reduce the viability of the micro-organisms used in the probiotics during storage. Cryoprotectants incorporated during freeze drying of the probiotic could enhance the shelf-life of the probiotic micro-organisms. Thus, in this investigation, the main objective was to determine the best combination of cryoprotectants to enhance the viability of Lactobacillus brevis I25 and L. reuteri C10 during freeze-drying by using the response surface methodology (RSM). A five-level, three-variable central composite rotatable design (CCRD) was used to evaluate the interactive effects of skim milk, sucrose and lactose as cryoprotectants, on the viability of L. brevis I25 and L. reuteri C10 during freeze drying. The inputs, log cfu/ml, were derived experimentally and tested by RSM. The models were found to describe adequately the experimental range studied. The optimum combination of cryoprotectants derived via RSM analysis were: 8% skim milk, 22% sucrose, 0.5% lactose for L. brevis I25 and 19.5% skim milk, 1% sucrose, 9% lactose for L. reuteri C10. The actual experimental results on the viability of L. brevis I25 and L. reuteri C10 after freeze-drying were 8.88 and 8.83 log cfu/ml, respectively, under optimum formulation. These values were highly comparable to the predicted values by RSM method of SAS/STAT which were 8.82 log cfu/ml for L. brevis I25 and 8.89 log cfu/ml for L. reuteri C10. The log cfu/ml values for controls (freeze-dried without cryoprotectants) were 7.65 and 7.2 for L. brevis I25 and L. reuteri C10, respectively. During the six month storage study at 4oC and 30oC, the optimum cryoprotectant combination for L. brevis I25 had a very high survival rate at 4oC but not at 30oC. On the other hand, the survival rate of the best combination for L. reuteri C10 was very high at both temperatures during storage. There was 0% residual viability for control culture after 16 weeks of storage for L. brevis I25 at 4oC and after 4 weeks at 30oC. For L. reuteri C10 after 12 and 8 weeks no bacterial growth were detected at 4oC and 30oC, respectively. The organic acids and amylase activity of bacterial cultures were also analysed during storage. The results showed that during storage at 4oC, the acetic acid concentration decreased from 144 mM to 100.25 mM for L. brevis I25 and from 153 mM to 115.6 mM for L. reuteri C10. In the case of lactic acid, the concentration decreased from 294 mM to 215 mM for L. brevis I25 and 205 mM to 124 mM for L. reuteri C10. The concentration of succinic acid also decreased from 2.9 mM to 1.2 mM for L. brevis I25 and from 17 mM to 9.4 mM for L. reuteri C10. There was also a reduction in amylase activity from 0.2 U to 0.11 U for L. brevis I25 and from 0.34 U to 0.18 U for L. reuteri C10. Acid production and amylase activity patterns for both Lactobacillus strains correspond to the survival rate of the bacteria during storage at 30oC.